Strategi Komunikasi Pemasaran PT Citiasia Internasional dalam Mengembangkan Aplikasi Inidesaku - Nida Nabila Putri; Jamiati KN (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
Indonesia has entered the digitalization era by utilizing technology. However, the gap in understanding between urban and rural communities is one of the obstacles to technological development in this country. PT Citiasia Internasional created the Inidesaku application which is aimed at building village communities so that they can compete in this era. In marketing the application, a marketing communication strategy is needed to achieve company goals. This made researchers interested in conducting research with the title